Bibliometric Mapping Analysis of Digital Innovation in Streamlining Bureaucratic Processes - Hasibuan, Ledia Sari; Yuliani, Sri; Ansoriyah, Faizatul (Dinasti Publisher, 2025)
Mapping bibliometric analysis of digital innovation in streamlining bureaucratic processes aims to identify and analyze the impact of digital technology implementation in improving bureaucratic efficiency and map the development of key themes in this field. This research was conducted by analyzing 354 relevant publications related to digital transformation in organizational management. The purpose of this study is to explore the relationship between digital innovation and bureaucratic efficiency, and to identify the challenges and opportunities that come with the application of technology in bureaucratic structures. The method used is bibliometric analysis which involves searching, mapping and analyzing relevant literature using bibliometric software to identify research patterns and emerging trends. The results show that digital innovation contributes greatly to improving efficiency through automation, standardization, and agility in bureaucratic structures. Nonetheless, there are potential drawbacks that need to be considered, such as over-reliance on technology that can reduce the role of humans in decision-making and organizational creativity. This mapping provides deeper insights into how digital innovations can streamline bureaucracy, while also reminding the importance of maintaining a balance between technology and human oversight in managerial processes.